Analisis penerimaan pajak reklame pada Badan Pendapatan Daerah Kota Manado - Arman, Haryanti; Walandouw, Stanley Kho; Wangkar, Anneke (Yayasan Widyantara Nawasena Raharja, 2025)
Regional autonomy and fiscal decentralisation require local governments to manage their finances and become self-governing. One of them is by exploring the potential of local revenue through local taxes. Billboard tax is included in the district/city local tax, so it is important to evaluate the implementation of the law at the local level, especially in Manado City. This study aims to analyze the effectiveness and contribution of advertising tax revenue to the Manado City Regional Original Income (PAD) at the Regional Revenue Agency during the period 2020 to 2022. The method used in this study is a descriptive qualitative method used by processing data through calculating the percentage of effectiveness and contribution based on a comparison between the realization and target revenue and PAD realization. The results of the study show that the level of effectiveness of advertising tax revenue has increased every year. Meanwhile, the contribution of advertising tax to the Manado City PAD has decreased from year to year. This shows that the role of advertising tax as a source of PAD is still very low and has not made a significant contribution to regional income.